Tratamiento de las aguas del sector las Katyas del estero El Macho en Machala mediante la Thalassiosira y Tetraselmis - Jaramillo Ramos, Ronald Augusto (2018)
The pollution of the Estero The male due to the banana activity is an environmental problem, since the discharges of wastewater with arsenic and lead from the banana plantations bordering this estuary harm the plants, animals, water resource and health of the people , quantitative and qualitative methodologies were used to establish this problem. Water analysis was carried out in some sectors of the El Macho estuary to determine the concentrations of the arsenic and lead metals in their waters, based on the results of the analyzes given in the Las Katyas Sector where the maximum concentrations were determined. 0.13mg / L and 0.06mg / L for As (arsenic) and Pb (lead) respectively, these concentrations exceed the maximum permissible limits established by Book VI Annex 1 of the TULSMA, that is why a proposal was prepared for the treatment of the metals As (arsenic) and Pb (lead) in the waters of the Las Katyas sector of this estuary through the microalgae of the genus Thalassiosira and Tetraselmis, this treatment plant is mainly constituted by a microalgae cultivation plant, a primary lagoon and a stabilization lagoon, it should be noted that previously based on an experimental investigation, the capacity of these microalgae for the absorption of the metals As (arsenic) and Pb (lead) present in the water.